Understanding and designing post-build rolling for mitigation of residual stress and distortion in wire arc additively manufactured components - Gornyakov, Valeriy; Ding, Jialuo; Sun, Yongle; Williams, Stewart (Elsevier, 2021)
Post-build rolling can mitigate residual stress (RS) and distortion in large-scale components built by wire arc additive manufacturing (WAAM). In this study, based on numerical simulations that considered both WAAM deposition and vertical rolling, the mechanisms of rolling-enabled mitigation of RS and distortion in a WAAM-built steel wall are elucidated. The influences of process configuration and condition, such as roller design (flat, profiled and slotted rollers), rolling load (25–75 kN) and roller-to-wall friction coefficient (0–0.8) on the distributions of plastic strain (PS) and RS were investigated. It is found that the slotted roller is most effective to introduce tensile PS for counteracting the compressive PS generated by the WAAM deposition, thereby reducing the tensile RS in the clamped condition and the final distortion after removal of clamps. Higher rolling load increases the rolling-induced tensile PS, which leads to more extensive mitigation of the WAAM-generated tensile RS. The simulations also demonstrate that the friction coefficient significantly affects the PS and RS when the slotted roller is employed. However, the efficacy of the flat/profiled roller is insensitive to friction coefficient. This study could underpin the development of an optimal post-build rolling process for efficient mitigation of RS and distortion in WAAM components.
Keywords: Directed energy deposition; Cold working; Residual stress; Plastic deformation; Roller geometry; Rolling load